Bank dan Lembaga Keuangan Syariah Dalam Perspektif Al-Qur’an - Dewi Maharani; Taufiq Hidayat (MALIA: Journal of Islamic Banking and Finance, 2020)
The Qur'an is the main source of Islamic teachings and is a reference for Muslims in understanding the Shari'a. In the Al-Qur'an there is no text that mentions the word bank, but in practice banking has been done since the time of the Prophet Muhammad. The Qur'an and Sunnah only provide basic principles and philosophies, and emphasize prohibitions that must be avoided. Thus, all that has to be done is to identify the things that are prohibited by Islam.